Efficacy of small-volume gastrografin videofluoroscopic screening for detecting pharyngeal leaks following total laryngectomy. Issue 4 (16th April 2020) - Narayan, M; Limbachiya, S; Balasubramanian, D; Subramaniam, N; Thankappan, K; Iyer, S
Abstract: Objectives: Pharyngocutaneous fistulae are dreaded complications following total laryngectomy. This paper presents our experience using 3–5 ml gastrografin to detect pharyngeal leaks following total laryngectomy, and compares post-operative videofluoroscopy with clinical follow-up findings in the detection of pharyngocutaneous fistulae. Methods: A retrospective case–control study was conducted of total laryngectomy patients. The control group ( n = 85) was assessed clinically for development of pharyngocutaneous fistulae, while the study group ( n = 52) underwent small-volume (3–5 ml) post-operative gastrografin videofluoroscopy. Results: In the control group, 24 of 85 patients (28 per cent) developed pharyngocutaneous fistulae, with 6 requiring surgical correction. In the study group, 24 of 52 patients (46 per cent) had videofluoroscopy-detected pharyngeal leaks; 4 patients (8 per cent) developed pharyngocutaneous fistulae, but all cases resolved following non-surgical management. Patients who underwent videofluoroscopy had a significantly lower risk of developing pharyngocutaneous fistulae; sensitivity and specificity in the detection of pharyngocutaneous fistulae were 58 per cent and 100 per cent respectively. Conclusion: Small-volume gastrografin videofluoroscopy reliably identified small pharyngeal leaks. Routine use in total laryngectomy combined with withholding feeds in cases of early leaks may prevent the development of pharyngocutaneous fistulae.